KETAHANAN RANTAI PASOK GLOBAL DAN IMPLIKASINYA TERHADAP REGULASI PERDAGANGAN INTERNASIONAL - Naek Efendi; Annie Myranika; Supendi; Tugimin Harjotaruno; Muhammad Ruhunussa; Asep Mulyana (CV. Lafadz Jaya, 2026)
Global supply chain resilience has become a central issue in international trade law in the wake of the COVID-19 pandemic, geopolitical conflicts, the energy crisis, climate change and the rise of new protectionist policies. Supply chain disruptions are no longer viewed as merely a business issue, but have evolved into an issue of international law that affects the stability of cross-border trade. This article analyses how global supply chain resilience impacts international trade regulation, including WTO rule reforms, the use of trade facilitation instruments, trade digitalisation, and policies on friendshoring, reshoring, and national economic security. The research employs a normative legal methodology using a legislative approach, a conceptual approach, and a comparative approach. The research findings indicate that international trade law needs to transform from an efficiency paradigm towards a resilience paradigm that continues to uphold the principles of non-discrimination, transparency, and legal certainty.